2010
DOI: 10.1016/j.juro.2010.03.131
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency of Epigenetic Events in Urothelial Tumors in Young Patients

Abstract: Urothelial tumors in patients younger than 19 years have a low rate of epigenetic alteration. Tumors in patients older than 20 years have epigenetic profiles similar to those of tumors in patients within the typical bladder urothelial cell carcinoma age range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The study showed low incidence of global hypermethylation in patients <20 years of age with an average methyl index of 34.4% versus 60.0% and 52.3% for the 2 older groups. 79 There was significantly less methylation in patients <20 years of age at the adenomatous polyposis coli, Bcl2, O 6 -methylguanine-DNA methyltransferase, and E-cadherin loci compared with the 2 older groups. 79 Relative methyl quantification showed that there were significantly higher concentrations of methylated alleles for O 6 -methylguanine-DNA methyltransferase and adenomatous polyposis coli in the oldest versus the 2 younger groups.…”
Section: Molecular Featuresmentioning
confidence: 88%
See 3 more Smart Citations
“…The study showed low incidence of global hypermethylation in patients <20 years of age with an average methyl index of 34.4% versus 60.0% and 52.3% for the 2 older groups. 79 There was significantly less methylation in patients <20 years of age at the adenomatous polyposis coli, Bcl2, O 6 -methylguanine-DNA methyltransferase, and E-cadherin loci compared with the 2 older groups. 79 Relative methyl quantification showed that there were significantly higher concentrations of methylated alleles for O 6 -methylguanine-DNA methyltransferase and adenomatous polyposis coli in the oldest versus the 2 younger groups.…”
Section: Molecular Featuresmentioning
confidence: 88%
“…79 There was significantly less methylation in patients <20 years of age at the adenomatous polyposis coli, Bcl2, O 6 -methylguanine-DNA methyltransferase, and E-cadherin loci compared with the 2 older groups. 79 Relative methyl quantification showed that there were significantly higher concentrations of methylated alleles for O 6 -methylguanine-DNA methyltransferase and adenomatous polyposis coli in the oldest versus the 2 younger groups. Tumor necrosis factor receptor superfamily member 25, endothelin receptor type B, and cyclin D2 hypermethylation occurred in patients <20 years of age and were not significantly different when compared with the 2 older patient groups.…”
Section: Molecular Featuresmentioning
confidence: 88%
See 2 more Smart Citations
“…Occupational exposure is another known risk factor for urothelial tumors in old patients, but its role is uncertain in young patients. Although urothelial tumors in young patients may lack some genetic alterations that are frequently observed in old patients [21,22], genetic factors are likely to play an important role in the early onset of urothelial tumors in young patients.…”
Section: Commentmentioning
confidence: 99%